2003
DOI: 10.1002/art.11347
|View full text |Cite
|
Sign up to set email alerts
|

Indentation testing of human cartilage: Sensitivity to articular surface degeneration

Abstract: Objective. To determine, for clinical indentation testing of human articular cartilage, the effects of aging and degeneration on indentation stiffness and traditional indices of cartilage degeneration; the relationship between indentation stiffness and indices of degeneration; and the sensitivity and specificity of indentation stiffness to cartilage degeneration.Methods. Results. Indentation stiffness, India ink staining, and the histopathology score each varied markedly between normal-sample and degenerate-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 47 publications
4
105
0
1
Order By: Relevance
“…Furthermore, in two of the three tibial plateaus, when the average [GAG] was computed over the full thickness, the correlation between [GAG] and indentation stiffness was eliminated. This result may help explain two previous studies in which mechanical properties were found not to correlate well with GAG, studies which involved full thickness GAG analyses in human knee articular surfaces exhibiting natural variation in cartilage integrity where one would expect the potential for considerable local spatial heterogeneity [5,16]. While the MRI and indentation studies here yielded high overall correlations between [GAG] and load response, clearly other factors must be considered.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, in two of the three tibial plateaus, when the average [GAG] was computed over the full thickness, the correlation between [GAG] and indentation stiffness was eliminated. This result may help explain two previous studies in which mechanical properties were found not to correlate well with GAG, studies which involved full thickness GAG analyses in human knee articular surfaces exhibiting natural variation in cartilage integrity where one would expect the potential for considerable local spatial heterogeneity [5,16]. While the MRI and indentation studies here yielded high overall correlations between [GAG] and load response, clearly other factors must be considered.…”
Section: Discussionsupporting
confidence: 61%
“…Abundant ex-vivo studies have shown that the load-bearing capacity of cartilage is dependent on the glycosaminoglycan (GAG) content. The structure-function relationship between GAG composition and mechanical properties has been observed in numerous studies examining normal, diseased, and experimentally-manipulated cartilages from humans and other species [1, 2,15,19,20,[22][23][24][25]30,37,411, although in some studies the relationship was not as clear [5,16]. Taken together, these past studies indicate a generally strong correspondence between bulk tissue GAG and mechanical properties, with most of the studies involving homogeneous normal cartilage samples or homogeneously-degraded cartilage samples, and all depended on bulk assays to provide the biochemical correlate.…”
Section: Introductionmentioning
confidence: 99%
“…In prior work by Bae et al, human cartilage plugs were analyzed by India ink staining and video image analysis to obtain a light reflectance score, with the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 purpose of characterizing this degeneration [10]. In these experiments, it was observed that India ink particles do not enter into healthy cartilage, but can be entrapped in irregular surfaces and will adhere to fibrillated cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the intensity of the cross‐linking, that is, ageing, the color of cartilage undergoes alterations from white (normal cartilage) to brown (cross‐linked cartilage) 16. To quantify possible color changes as an indication of the cross‐linking following incubation with l ‐threose, samples were placed side‐by‐side and digital images from the cartilage surface were captured from above (Samsung Galaxy S6, 12 Megapixels) at the same time during the day.…”
Section: Methodsmentioning
confidence: 99%